Neoseiulus californicus preying on Tenuipalpus heveae - Silva, Eliamara Marques da [UNESP]; Toscano, Luciana Claudia; Alves-Eigenheer, Milene [UNESP]; Maruyama, Wilson Itamar; Silva, Abimael Gomes da [UNESP] (Univ Federal Goias, 2020)
The spread of Tenuipalpus heveae Baker (Acari: Tenuipalpidae) can be controlled by managing predatory species such as Neoseiulus californicus (McGregor) ( Acari: Phytoseiidae). This study aimed to evaluate the predation of N. californicus at different biological phases on T. heveae at different development stages. The experiments were carried out under laboratory-controlled conditions, counting the number of predated individuals by development stage after 24, 48 and 72 h. N. californicus, in all phases, consumed T. heveae, with a higher consumption of nymphs and larvae by adult predators. Both sexes of adult predators exhibited predation efficiency, but females showed a greater acceptance of adult preys than males. The daily rate of adult predation decreased over time; however, the highest consumption took place in the first 24 h.
Keywords: Phytoseiidae; biological control; predatory mite